4 Arab american adolescents' bullying experiences and effects on their perceived stress and health. (19th September 2017) - Albdour, Maha; Lewin, Linda; Yarandi, Hossein; Hong, Jun; Wilson, Feleta
Abstract : Arab American Adolescents' Bullying Experiences and effects on their Perceived Stress and Health Purpose and Background/Significance: This study is intended to examine the bullying experience among Arab American adolescents and effects on their perceived stress and health. Adolescents who are vulnerable or marginalised might be at higher risk for bullying. Arab American adolescents have not been included in research studies examining bullying and described as the invisible population. Method: Utilising a community-based approach and cross- sectional, correlational descriptive design, a convenient sample of 150 Arab American adolescents ages12 to 16 were recruited from two community centres, located at southeastern Michigan. Adolescents completed a survey about their bullying experience, their stress levels and if they experience any physical or psychological symptoms in the last year. Measurements included are the Adolescents Peer Relation Instrument (APRI), the Perceived Stress Scale (PSS-10), the Children's Somatization Inventory (CSI-24) and Kessler Psychological Distress Scale (K10). Multiple regression and correlation statistics were used to examine the relationships between the study variables. Results: Initial results shows that adolescents who were victims of bullying experienced high stress levels, increased somatic complaints and psychological distress. In contrast, bullies did not reported high stress levels but indicated significant somatic complaints and psychological distress. Conclusions: Bullying experience was associated with negative physical and psychological health outcomes as well as increased levels of stress among victims. Nurses and other primary health care providers can screen adolescents for physical symptoms and stress related to bullying. In addition providing culturally tailored prevention and intervention strategies may help to promote the overall health of adolescents who experience bullying by increasing their resistance to stress and developing supportive coping mechanisms.